Forest certification as a tool for ensuring sustainable management of forest in the Philippines prospects and challenges - Dolom, P.C.; Bugayong, L.A.; Casin, M.C.S.; Tolentino, N. L.; Palacpac, A. B.; Villanueva, M.M.B. (2016)
Forest certification is a tool that promotes sustainable forest management. It is a market-based, voluntary instrument introduced in the early 1990s to address mounting concerns related to deforestation in the tropics and improve forest management (Rametsteiner & Simula 2003). Forest certification includes two basic components, forest management certification and chain of custody (CoC) certification. Forest management certification is issued as proof that a forest management unit (FMU) is sustainably managed. CoC certification, on the other hand, is a comprehensive assessment on the whole chain of custody from the processing, manufacturing, storage to the final consumers, to verify the origin of the raw materials involved (Nussbaum and Simula 2005). This paper aims to present the policy proposals on the establishment of a Philippine forest certification system towards SFM developed by the Forestry Development Center, University of the Philippines Los Baños College of Forestry and Natural Resources (FDC, UPLB-CFNR) and the Forest Management Bureau, Department of Environment and Natural Resources (FMB-DENR). The paper discusses the forest certification policies, standards, accreditation process, and the draft Executive Order (EO) and Department Administrative Order (AO) to establish the forest certification system in the country. It also presents the potentials for forest certification as well as the challenges in implementing it.
Keywords: Forest management; Forests and forestry; Forestry laws and legislation